Technical Efficiency of Vannamei Shrimp (Litopenaeus Vannamei) Farming in West Java Province (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
Shrimp is one of Indonesia's leading fishery commodities. Vaname shrimp is the most widely cultivated type of shrimp. Shrimp production fluctuates every year. West Java is one of the shrimp centers that experienced a greater decline in production compared to other shrimp center provinces. This decline in production may be attributed to a failure to achieve technical efficiency. This study aims to determine the technical efficiency level by including variables affecting production and technical efficiency. This study was conducted in Indramayu Regency, which is one of the shrimp centers in West Java. This study employs the Stochastic Frontier Analysis (SFA) method, utilizing the Cobb-Douglas production function. The results showed that shrimp farmers in Indramayu Regency are technically efficient, with an efficiency value of 0.83. Factors affecting production are fry, feed, in-family labor, out-of-family labor, and water pumps. Factors affecting technical efficiency are age, experience, number of dependents, and capital sources. This study suggests that feed is the most responsive variable to production, so good feed management is needed. Young farmers are more efficient, so this business can be an alternative for the younger generation